Infections caused by mycobacterium tuberculosis in patients with hematological disorders and in recipients of hematopoietic stem cell transplant, a twelve year retrospective study - Al-Jasser Asma; Al-Anazi Khalid; Evans David (BMC, 2007)
Abstract Background Tuberculous infections in patients with hematological disorders and hematopoietic stem cell transplant vary in incidence, complications and response to treatment. Methods and materials A retrospective study of patients with various benign and malignant hematological disorders and recipients of hematopoietic stem cell transplant who were treated at Riyadh Armed Forces Hospital, Saudi Arabia between January 1991 and December 2002 and who developed tuberculous infections was conducted. Results Tuberculous infections occurred in eighteen patients with hematological disorders and hematopoietic stem cell transplant. The main associated factors were: reduced immunity due to the primary hematological disorder, age more than 50 years and the administration of cytotoxic chemotherapy, steroids or radiotherapy. These infections frequently involved the lungs and predominantly occurred in males and in patients with chronic myeloproliferative disorders, myelodysplastic syndrome and acute myeloid leukemia. In patients treated with intravenous cytotoxic chemotherapy, tuberculous infections tended to occur earlier and also tended to be more disseminated compared to infections occurring in patients treated with oral chemotherapy. Anti-tuberculous treatment was given to 16 patients and it was successful in 15 of these patients. Conclusion Tuberculous infections cause significant morbidity and mortality in patients with various hematological disorders and in recipients of hematopoietic stem cell transplant. The early administration of anti-tuberculous therapy and compliance with drug treatment are associated with successful outcomes while delayed management, drug resistance and the presence of miliary infections are associated with poor prognosis and high mortality rates.